Soft and hard carbon coated nanometer silicon-silicon monoxide composite negative electrode material
Through the combination of mechanical ball milling and microstructure regulators, the stability and cost of Si-based anode materials in lithium-ion batteries are solved, and a soft and hard carbon-coated nano-silicon-oxide composite anode material is produced, which improves the electrode material The cyclic performance and conductivity simplify the process flow.
Patent Information
- Application Number
- CN202411681604.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The Si-based anode material in existing lithium-ion batteries has stability problems due to volume expansion, poor conductivity and unstable SEI films. The preparation method relies on high-cost organic solvents and complex processes, resulting in poor rate performance and cycle performance.
Mechanical ball milling is performed by hydrophobic nanosilicon oxide and asphalt to form a stable asphalt-coated nanosilicon oxide suspension, combined with microstructure regulators and low-temperature aluminum thermal reduction, to produce soft and hard carbon-coated nanosilicon-silicon oxide composite The negative electrode material avoids the use of organic solvents and bonding blocking problems.
It achieves uniform coating, reduces costs, improves the circulation and conductivity of the negative electrode material, simplifies the process flow, is suitable for mass production, and improves the rate performance and capacity retention of the electrode material.
Smart Images

Figure CN119275240A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery electrode materials, and in particular relates to a soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material. Background Art
[0002] Silicon (Si) is a representative anode material for next-generation lithium-ion batteries due to its high theoretical capacity, suitable working potential, and high natural abundance. However, due to the inherent volume expansion (up to 300%) during the lithiation / delithiation process, as well as poor conductivity and unstable solid electrolyte interface (SEI) film, Si-based anodes have serious stability issues, which greatly hinder their practical applications. To address these issues, carbon-modified Si anodes are a promising approach that has been shown to effectively alleviate the inherent volume expansion problem of Si anodes during lithiation / delithiation as well as improve the conductivity and material plasticity of anode materials.
[0003] The soft and hard carbon composite modified Si negative electrode has a high research value. Soft carbon has good toughness. The soft carbon film coated on the surface of nano-Si is not easy to crack and fall off during the charge and discharge process. The porous structure of hard carbon can absorb the huge volume expansion of Si, release the stress caused by the volume change of Si, and improve the cycle performance of the negative electrode material. In addition, soft carbon has a high structural order and good conductivity, while hard carbon has more defects and can provide more Li + At the embedding point, the composite coated Si negative electrode can effectively improve the conductivity of the entire negative electrode material, ensuring that electrons can be smoothly conducted, thereby improving the rate performance of the negative electrode material.
[0004] At present, the common preparation method of commercial Si / C composite negative electrode materials is to uniformly disperse nano-Si in asphalt / carbon tetrachloride (CCl 4 ) or asphalt / tetrahydrofuran (C 4 H 8 O) solution to prepare asphalt / Si precursor, and then heat-treat in an inert atmosphere to obtain Si / C composite negative electrode material. However, this method of preparing Si / C composite negative electrode material has obvious disadvantages: first, in order to fully dissolve the asphalt and evenly coat it on the surface of nano-Si, this preparation method uses a large amount of CCl 4 , C 4 H 8 O and other organic solvents, resulting in a high cost of the final Si / C composite negative electrode material; secondly, the asphalt / Si precursor prepared by this preparation method, during the inert atmosphere heat treatment process, the asphalt is very easy to stick and agglomerate, and the prepared Si / C negative electrode material presents a very dense rock-like microstructure, resulting in poor rate performance and cycle performance of the prepared negative electrode material. Therefore, this preparation method relies on further ball milling and secondary coating treatment, which is complex and inefficient. Summary of the invention
[0005] The purpose of the present invention is to overcome the above problems existing in the conventional technology and provide a soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material. The present invention adopts hydrophobic nano-silicon oxide and asphalt as the main raw materials, and adopts mechanical ball milling to prepare a suspension system of asphalt-coated nano-silicon oxide; the prepared suspension system is slowly added with a microstructure regulator, heated and stirred, and then dried and heat-treated in an inert atmosphere to obtain carbon-coated nano-silicon oxide powder, and finally a soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material is obtained by low-temperature aluminum thermal reduction.
[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0007] The present invention provides a soft and hard carbon coated nano silicon-silicon oxide composite negative electrode material. The raw materials for preparing the composite negative electrode material include a silicon source and asphalt. The silicon source is hydrophobic nano silicon oxide with an average particle size of 10 to 80 nm. The asphalt is asphalt with a residual carbon content of 15 to 25% after heat treatment at 1000°C in an inert atmosphere.
[0008] The method for preparing the composite negative electrode material comprises the following steps:
[0009] 1) According to a certain mass ratio, an appropriate amount of hydrophobic nano-silicon oxide and asphalt are placed in a stainless steel ball mill, the ball mill is placed in an insulating heat preservation jacket, and the ball mill is controlled at a certain speed for a period of time to obtain asphalt-coated hydrophobic nano-silicon oxide;
[0010] 2) Mixing the prepared asphalt-coated hydrophobic nano-silicon oxide with an appropriate amount of an emulsifier and a stabilizer in a certain mass ratio, and ball milling at a certain speed at room temperature for a period of time to obtain a stable suspension system of asphalt-coated nano-silicon oxide;
[0011] 3) Slowly adding the prepared suspension system of asphalt-coated nano-silicon oxide into the microstructure regulator according to a certain mass ratio, stirring for a period of time at a certain temperature, and obtaining a brown paste product;
[0012] 4) The brown paste precursor is vacuum dried and then heat treated at a certain temperature in an inert atmosphere for a period of time to obtain carbon-coated nano-silicon oxide powder, which is then reduced by aluminum heat to obtain soft and hard carbon-coated nano-silicon-silicon oxide.
[0013] Furthermore, in step 1), the mass ratio of hydrophobic nano-silicon oxide to asphalt is 1:1.0 to 1.5.
[0014] Furthermore, in step 1), the rotation speed of the ball mill is 350-450 rpm, the mass ratio of the material in the jar to the grinding balls is 1:30-40, and the temperature of the ball mill jar is controlled at 90-120°C.
[0015] Furthermore, in step 2), the emulsifier is a solution of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate or sodium stearate with a concentration of 2 to 5 wt %; the mass ratio of asphalt to the solute in the emulsifier is 1:0.05 to 0.15.
[0016] Furthermore, in step 2), the stabilizer is a sodium hydroxide solution with a concentration of 0.2 to 1.0 wt%, and the mass ratio of asphalt to the solute in the stabilizer is 1:0.005 to 0.020.
[0017] Furthermore, in step 2), the rotation speed of the ball mill is 350-450 rpm, and the mass ratio of the material in the tank to the grinding balls is 1:30-40.
[0018] Furthermore, in step 3), the microstructure modifier is citric acid-ethylene glycol sol, polyvinyl alcohol solution or monohydrated citric acid solution, and the mass ratio of hydrophobic nano-silica to the microstructure modifier is 1:60-90.
[0019] Furthermore, in step 3), the hydrophobic nano-silicon oxide / asphalt suspension and the microstructure regulator are mixed and stirred at a temperature of 55 to 65° C. for a stirring time of 6 to 10 hours.
[0020] Furthermore, in step 4), the heat treatment temperature in the inert atmosphere is 900-1100° C., and the heat treatment time is 2-4 hours.
[0021] The present invention also provides the use of the soft and hard carbon coated nano silicon-silicon dioxide composite negative electrode material in the preparation of lithium ion battery electrode materials.
[0022] The present invention is mainly based on the following technical principles: (1) The present invention does not use organic solvents (CCl 4 , C 4 H 8O, etc.) can also make asphalt and hydrophobic nano-silicon oxide uniformly compounded. This is because during the heat-insulating ball milling of asphalt and hydrophobic nano-silicon oxide, mechanical energy is continuously converted into thermal energy, the temperature in the ball milling tank rises rapidly to 80-110°C, and the asphalt is converted from a solid state to a molten state. The molten asphalt and the used nano-silicon oxide both have hydrophobic properties. The interface energy between the molten asphalt and the nano-silicon oxide is very small. The molten asphalt is spontaneously coated on the surface of the hydrophobic nano-silicon oxide. In the subsequent ball milling process mixed with an emulsifier and a stabilizer, the coarse nano-silicon oxide particles coated with the asphalt are continuously broken into ultrafine particles due to the shear force generated by the ball milling. The lipophilic end of the emulsifier molecule is adsorbed on the surface of the nano-silicon oxide coated with the asphalt to form micelles of appropriate density, and finally a nano-silicon oxide suspension system uniformly coated with asphalt is obtained. (2) The present invention can effectively overcome the problem that the asphalt adheres and agglomerates during the heat treatment process to form a dense block microstructure, resulting in the poor electrochemical performance of the final composite electrode material. This is because during the heating and stirring process, the asphalt-coated nano-silicon oxide solid-liquid suspension system is added to the microstructure regulator, the asphalt-coated nano-silicon oxide ultrafine particles are wrapped by the microstructure regulator, and the contact between the asphalt-coated nano-silicon oxide particles is blocked. Therefore, in the subsequent drying and inert atmosphere heat treatment process, the adhesion and agglomeration of the asphalt are avoided to form a dense block microstructure; after the inert atmosphere heat treatment, the soft carbon formed by the pyrolysis of the asphalt is coated on the surface of the nano-silicon oxide, and the hard carbon formed by the pyrolysis of the microstructure regulator solute is dispersed between the soft carbon-coated nano-silicon oxide particles (SiO 2 @C), and finally, low-temperature aluminothermic reduction is performed to achieve the soft and hard carbon coating of nano-silicon-silicon oxide (nano-Si / SiO x @C).
[0023] The beneficial effects of the present invention are:
[0024] 1. The present invention achieves uniform coating of hydrophobic nano-silicon oxide with asphalt by ball milling the asphalt / hydrophobic nano-silicon oxide at 80-110°C, and converts the asphalt-coated nano-silicon oxide into a stable solid-liquid suspension system by using mechanical ball milling technology and cheap emulsifiers and stabilizers, thus avoiding the need to use more CCl in the current Si / C negative electrode material asphalt-coated nano-Si. 4 , C 4 H 8 Organic solvents such as O cause the final negative electrode material cost to be high.
[0025] 2. The present invention drips the asphalt-coated nano-silicon oxide suspension system into the microstructure regulator, and the microstructure regulator solute is coated on the surface of the ultrafine particles of the suspension after heating and stirring, which effectively prevents the re-agglomeration of nanoparticles caused by the adhesion and agglomeration of asphalt, and avoids the formation of dense block microstructures due to the adhesion and agglomeration of asphalt in the prepared negative electrode material, resulting in poor rate performance and cycle performance.
[0026] 3. The present invention realizes nano-Si / SiO x The soft and hard carbon composite coating of asphalt pyrolysis has good toughness and is coated on nano-Si / SiO x The surface is not easy to crack or fall off during the charge and discharge process, and the hard carbon pyrolyzed by the microstructure regulator solute has a porous structure, which is coated on the pitch carbon coated nano-Si / SiO x The surface can absorb nano-Si / SiO x The volume expansion of the battery can release the stress caused by the volume change and improve the cycle performance of the negative electrode material. In addition, the soft and hard carbon composite coating can effectively improve the conductivity of the entire material, ensuring that electrons can be smoothly conducted, thereby improving the rate performance of the electrode material.
[0027] 4. The preparation method of the present invention has the characteristics of simple process, simple equipment, low cost and environmental friendliness, and is easy to achieve mass production. The prepared silicon-carbon negative electrode material has a current density of 0.05A g -1 The first cycle discharge / charge capacity is 2713.8 / 1670.6mAh g -1 The first coulombic efficiency is 61.6%; when the current density is increased to 2.0A g -1 The measured reversible capacity is 748.7 mAh g -1 , the capacity retention rate is as high as 46.9%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 561.0 mAh g -1 , the capacity retention rate is 79.6%.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1 The nano-Si / SiO prepared in Example 1 x @XRD pattern of C negative electrode material;
[0031] Figure 2 The nano-Si / SiO prepared in Example 1 x @C XPS diagram of negative electrode material;
[0032] Figure 3 The nano-Si / SiO prepared in Example 1 x @FESEM image of C negative electrode material;
[0033] Figure 4 The nano-Si / SiO prepared in Example 1 x @TEM image of C negative electrode material;
[0034] Figure 5 The nano-Si / SiO prepared in Example 1 x @C negative electrode material assembled battery sample at 0.05A g -1 Constant current charge and discharge curve under current density;
[0035] Figure 6 The nano-Si / SiO prepared in Example 1 x @C rate curves of assembled battery samples with negative electrode materials at different current densities;
[0036] Figure 7 The nano-Si / SiO prepared in Example 1 x @C negative electrode material assembled battery samples at 0.5A g -1 Cycling performance curve under current density. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present invention achieves uniform coating of asphalt on hydrophobic nano-silicon oxide by ball milling asphalt / hydrophobic nano-silicon oxide at 80-110°C, and uses mechanical ball milling, with the help of cheap emulsifiers and stabilizers, to coat asphalt-coated nano-silicon oxide (asphalt / SiO 2 ) into a stable solid-liquid suspension system; dropping the asphalt-coated nano-silicon oxide suspension system into the microstructure regulator, the asphalt / SiO 2 The particles are coated and isolated by the microstructure regulator, which prevents the asphalt / SiO 2 The particles adhere to each other to form a dense block structure, and the soft and hard carbon coating of hydrophobic nano-silicon oxide is achieved by heat treatment in an inert atmosphere. By means of low-temperature aluminum thermal reduction, the soft and hard carbon-coated nano-Si / SiO x This soft and hard carbon-coated nano-Si / SiO xThe preparation method of the composite negative electrode material is not only simple in process, high in efficiency, low in cost, environmentally friendly, and easy to achieve large-scale production, but also the prepared lithium-ion battery negative electrode material has excellent comprehensive electrochemical properties.
[0039] The present invention achieves uniform coating of hydrophobic nano-silicon oxide by asphalt by ball milling asphalt and hydrophobic nano-silicon oxide at 80-110°C, and converts the asphalt-coated nano-silicon oxide into a stable solid-liquid suspension system by mechanical ball milling with the aid of cheap emulsifiers and stabilizers, thus overcoming the problem that the current preparation of Si / C negative electrode materials using asphalt as a carbon source relies on a large amount of organic solvents (CCl 4 、C4H 8 O, etc.), and solves the problem of high cost of the prepared Si / C composite negative electrode material. The present invention uses citric acid-ethylene glycol sol, polyvinyl alcohol solution, etc. as microstructure regulators to overcome the disadvantages of asphalt / SiO 2 The particles adhere and agglomerate during the heat treatment process to form a dense bulk structure, which leads to problems such as poor rate performance and cycle performance of the final composite negative electrode material.
[0040] The specific embodiments of the present invention are as follows:
[0041] Example 1
[0042] 1) According to the weight ratio of hydrophobic nano-silicon oxide to asphalt of 1:1.1667, 3.0002 g of nano-silicon oxide and 3.5001 g of asphalt were weighed and placed in a stainless steel ball mill, and the ball mill was placed in an insulating heat preservation jacket, and ball milled at 400 rpm for 8 h. The temperature of the ball mill was controlled at 110° C. The weight ratio of the material in the mill to the grinding ball was 1:40, and asphalt-coated hydrophobic nano-silicon oxide was obtained;
[0043] 2) According to the weight ratio of asphalt to solute in the emulsifier being 1:0.1 and the weight ratio of asphalt to solute in the stabilizer being 1:0.01, 17.5005 g of 2 wt% sodium dodecylbenzene sulfonate solution and 7.0002 g of 0.5 wt% NaOH solution were weighed and ball-milled at 400 rpm at room temperature for 6 h to obtain a stable asphalt-coated nano-silicon oxide suspension system;
[0044] 3) According to the molar ratio of citric acid monohydrate to ethylene glycol of 1:0.6667, 0.8602g of citric acid monohydrate and 0.1693g of ethylene glycol were weighed and dissolved in 50ml of deionized water, and the mixture was stirred at 70°C and pH 4 for 5h to obtain a citric acid-ethylene glycol sol. According to the weight ratio of hydrophobic nano-silica to microstructure regulator of 1:79.0910, 20.0012g of asphalt-coated nano-silica suspension system was weighed and dropped into the obtained citric acid-ethylene glycol sol, and the mixture was stirred at 60°C for 8h to obtain a brown paste product;
[0045] 4) The brown paste product was placed in a vacuum drying oven at 60°C for 6 h, and the dried product was placed in an argon atmosphere for heat treatment at 1000°C for 3 h to obtain soft and hard carbon-coated hydrophobic nano-silicon oxide, which was then subjected to low-temperature aluminothermic reduction to obtain soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode materials (abbreviated as Si / SiO x @C);
[0046] The negative electrode materials prepared according to the above steps were assembled into a half-cell, and the electrochemical performance was measured as follows: -1 The first cycle discharge / charge capacity is 2713.8 / 1670.6mAh g -1 The first coulombic efficiency is 61.6%; when the current is increased to 2.0A g -1 The measured reversible capacity is 748.7 mAh g -1 , the capacity retention rate is as high as 46.9%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 561.0 mAh g -1 , the capacity retention rate is 79.6%.
[0047] Example 2
[0048] 1) According to the weight ratio of hydrophobic nano-silicon oxide to asphalt of 1:1.1667, 3.0002 g of nano-silicon oxide and 3.5001 g of asphalt were weighed and placed in a stainless steel ball mill, and the ball mill was placed in an insulating heat preservation jacket, and ball milled at 400 rpm for 8 h. The temperature of the ball mill was controlled at 110° C. The weight ratio of the material in the mill to the grinding ball was 1:40, and asphalt-coated hydrophobic nano-silicon oxide was obtained;
[0049] 2) According to the weight ratio of asphalt to solute in the emulsifier being 1:0.1 and the weight ratio of asphalt to solute in the stabilizer being 1:0.01, 17.5005 g of 2 wt% sodium dodecyl sulfate solution and 7.0002 g of 0.5 wt% NaOH solution were weighed and ball-milled at 400 rpm at room temperature for 6 h to obtain a stable asphalt-coated nano-silicon oxide suspension system;
[0050] 3) According to the molar ratio of citric acid monohydrate to ethylene glycol of 1:0.6667, 0.8602g of citric acid monohydrate and 0.1693g of ethylene glycol were weighed and dissolved in 50ml of deionized water, and mixed and stirred at 60-80°C and pH 4 for 5h to obtain a citric acid-ethylene glycol sol, and according to the weight ratio of hydrophobic nano-silica to microstructure regulator of 1:79.0910, 20.0012g of asphalt-coated nano-silica suspension system was weighed and dropped into the obtained citric acid-ethylene glycol sol, and continued to stir at 60°C for 8h to obtain a brown paste product;
[0051] 4) The brown paste product was placed in a vacuum drying oven at 60°C for 6 h, and the dried product was placed in an argon atmosphere for heat treatment at 1000°C for 3 h to obtain soft and hard carbon-coated hydrophobic nano-silicon oxide, which was then subjected to low-temperature aluminothermic reduction to obtain soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode materials (abbreviated as Si / SiO x @C);
[0052] The negative electrode materials prepared according to the above steps were assembled into a half-cell, and the electrochemical performance was measured as follows: -1 The first cycle discharge / charge capacity is 2675.3 / 1626.6mAh g -1 The first coulombic efficiency is 60.9%; when the current is increased to 2.0A g -1 The measured reversible capacity is 702.3 mAh g -1 , the capacity retention rate is as high as 43.5%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 523.4 mAh g -1 , the capacity retention rate is 75.8%.
[0053] Example 3
[0054] 1) According to the weight ratio of hydrophobic nano-silicon oxide to asphalt of 1:1.1667, 3.0002 g of nano-silicon oxide and 3.5001 g of asphalt were weighed and placed in a stainless steel ball mill, and the ball mill was placed in an insulating heat preservation jacket, and ball milled at 400 rpm for 8 h. The temperature of the ball mill was controlled at 110° C. The weight ratio of the material in the mill to the grinding ball was 1:40, and asphalt-coated hydrophobic nano-silicon oxide was obtained;
[0055] 2) According to the weight ratio of asphalt to solute in the emulsifier being 1:0.1 and the weight ratio of asphalt to solute in the stabilizer being 1:0.01, 17.5005 g of 2 wt% sodium dodecylbenzene sulfonate solution and 7.0002 g of 0.5 wt% NaOH solution were weighed and ball-milled at 400 rpm at room temperature for 6 h to obtain a stable asphalt-coated nano-silicon oxide suspension system;
[0056] 3) Weigh 1.0295 g of PVA and dissolve it in 50 ml of deionized water, heat and reflux at 80 ° C with stirring for 8 h to obtain a PVA solution, and weigh 20.0012 g of the suspension system of asphalt-coated nano-silica in a weight ratio of 1:79.0910 to the microstructure regulator, and drop it into the prepared citric acid-ethylene glycol sol, and continue stirring at 60 ° C for 8 h to obtain a brown paste product;
[0057] 4) The brown paste product was placed in a vacuum drying oven at 60°C for 6 h, and the dried product was placed in an argon atmosphere for heat treatment at 1000°C for 3 h to obtain soft and hard carbon-coated hydrophobic nano-silicon oxide, which was then subjected to low-temperature aluminothermic reduction to obtain soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode materials (abbreviated as Si / SiO x @C);
[0058] The negative electrode materials prepared according to the above steps were assembled into a half-cell, and the electrochemical performance was measured as follows: -1 The first cycle discharge / charge capacity is 2589.7 / 1566.8mAh g -1 The first coulombic efficiency is 60.5%; when the current is increased to 2.0A g -1 The reversible capacity was 723.4 mAh g -1 , the capacity retention rate is as high as 41.9%; at 0.50A g -1 After 200 cycles, the capacity of the electrode material is still as high as 501.8 mAh g -1 , the capacity retention rate is 75.5%.
[0059] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A soft and hard carbon coated nano silicon-silicon oxide composite negative electrode material, characterized in that: The raw materials for preparing the composite negative electrode material include a silicon source and asphalt, wherein the silicon source is hydrophobic nano silicon oxide with an average particle size of 10 to 80 nm, and the asphalt is asphalt with a residual carbon content of 15 to 25% after heat treatment at 1000°C in an inert atmosphere; The method for preparing the composite negative electrode material comprises the following steps: 1) According to a certain mass ratio, an appropriate amount of hydrophobic nano-silicon oxide and asphalt are placed in a stainless steel ball mill, the ball mill is placed in an insulating heat preservation jacket, and the ball mill is controlled at a certain speed for a period of time to obtain asphalt-coated hydrophobic nano-silicon oxide; 2) Mixing the prepared asphalt-coated hydrophobic nano-silicon oxide with an appropriate amount of an emulsifier and a stabilizer in a certain mass ratio, and ball milling at a certain speed at room temperature for a period of time to obtain a stable suspension system of asphalt-coated nano-silicon oxide; 3) Slowly adding the prepared suspension system of asphalt-coated nano-silicon oxide into the microstructure regulator according to a certain mass ratio, stirring for a period of time at a certain temperature, and obtaining a brown paste product; 4) The brown paste precursor is vacuum dried and then heat treated at a certain temperature in an inert atmosphere for a period of time to obtain carbon-coated nano-silicon oxide powder, which is then reduced by aluminum heat to obtain soft and hard carbon-coated nano-silicon-silicon oxide.
2. The soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 1), the mass ratio of hydrophobic nano-silicon oxide to asphalt is 1:1.0-1.
5.
3. The soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 1), the rotation speed of the ball mill is 350-450 rpm, the mass ratio of the material in the jar to the grinding balls is 1:30-40, and the temperature of the ball mill jar is controlled at 90-120°C.
4. The soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 2), the emulsifier is sodium dodecylbenzene sulfonate, sodium dodecyl sulfate or sodium stearate solution with a concentration of 2 to 5 wt %; the mass ratio of asphalt to the solute in the emulsifier is 1:0.05 to 0.
15.
5. The soft and hard carbon coated nano silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 2), the stabilizer is a sodium hydroxide solution with a concentration of 0.2-1.0 wt%, and the mass ratio of asphalt to the solute in the stabilizer is 1:0.005-0.
020.
6. The soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 2), the rotation speed of the ball mill is 350-450 rpm, and the mass ratio of the material in the tank to the grinding balls is 1:30-40.
7. The soft and hard carbon coated nano silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 3), the microstructure modifier is citric acid-ethylene glycol sol, polyvinyl alcohol solution or monohydrated citric acid solution, and the mass ratio of hydrophobic nano-silicon oxide to the microstructure modifier is 1:60-90.
8. The soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 3), the hydrophobic nano-silicon oxide / asphalt suspension and the microstructure control agent are mixed and stirred at a temperature of 55 to 65° C. for a stirring time of 6 to 10 hours.
9. The soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to claim 1, characterized in that: In step 4), the heat treatment temperature in the inert atmosphere is 900-1100° C., and the heat treatment time is 2-4 hours.
10. Use of the soft and hard carbon-coated nano-silicon-silicon oxide composite negative electrode material according to any one of claims 1 to 9 in the preparation of lithium-ion battery electrode materials.
Citation Information
Cited By
Preparation method of high-stability silicon-carbon material
CN120048887A